Refocusing Higher Education Budget Development - Illinois State Board of Higher Education, Springfield; Illinois State Board of Higher Education, Springfield ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1999)
This report outlines several recommendations for new or substantially revised budget development procedures set out by the Illinois State Board of Higher Education. They include: (1) a statewide budget context report prepared early in the budget process that will provide colleges and universities with information they can use in their own budget requests; (2) more inclusive budget meetings; (3) a closer link between statewide strategic goals and budget recommendations; (4) statewide strategic goals that include performance measures and assessments to enable the higher education community and individual institutions to assess progress; and (5) annual assessment of the collective progress of higher education toward achievement of the statewide strategic goals. Illinois colleges, universities, and higher education agencies are encouraged to ensure that their processes and schedules are compatible with the state-level process. (CH)
ERIC Note: For related document, see ED 422 746.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Budgeting; Educational Finance; Educational Planning; Higher Education; Institutional Administration; Policy Formation; Public Education; State Departments of Education; State Standards; Illinois; Opinion Papers